2006
DOI: 10.4269/ajtmh.2006.74.744
|View full text |Cite
|
Sign up to set email alerts
|

Mefloquine Use and Hospitalizations Among Us Service Members, 2002–2004

Abstract: The safety of mefloquine has not been well described in military populations. This study used standard military databases for mefloquine prescriptions and hospitalizations to investigate mefloquine safety among US service members from 2002 through 2004. Mefloquine-prescribed and deployed personnel (N = 8,858) were compared with two reference groups. The reference groups comprised US service members who were not prescribed mefloquine and resided in Europe or Japan (N = 156,203) or had been otherwise deployed (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…5,8,15,17,30 Specifically among U.S. military deployers, Wells and others reported no association between mefloquine prescriptions and hospitalizations for a wide range of outcomes. 5 Additional studies among deployed military populations reported mefloquine to be well tolerated, with the exception of individuals previously diagnosed with an NPO. 15,17,30 Contrary to our findings, other studies have reported an association between NPOs and mefloquine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,8,15,17,30 Specifically among U.S. military deployers, Wells and others reported no association between mefloquine prescriptions and hospitalizations for a wide range of outcomes. 5 Additional studies among deployed military populations reported mefloquine to be well tolerated, with the exception of individuals previously diagnosed with an NPO. 15,17,30 Contrary to our findings, other studies have reported an association between NPOs and mefloquine.…”
Section: Discussionmentioning
confidence: 99%
“…4 Serious adverse events after mefloquine use are rare. [5][6][7] Studies evaluating the occurrence of neuropsychiatric outcomes (NPOs) after mefloquine use report mixed results, but a large proportion of these studies found an association between mefloquine and NPOs. [7][8][9][10][11][12][13][14][15][16][17] Due to the extensive use of mefloquine for malaria prevention among service members before 2009 and its continued, limited use, after that point, the need to evaluate adverse events in service members who took the drug is evident.…”
Section: Introductionmentioning
confidence: 99%
“…Mefloquine is the best-documented drug for long-term travelers and, if well tolerated, can be used for prolonged periods; i.e., there is no upper time limits for the use of mefloquine (34). It has a simple weekly dosing schedule that encourages adherence (39), and toxic accumulation in the body does not occur during longterm use (14). Doxycycline (a tetracycline compound) is used for This means that long-term travelers must have knowledge about malaria as a disease, including key symptoms such as fever, the adequate use of SBET, the problems of counterfeit drugs, and the need to identify reliable health care facilities in case of emergency.…”
Section: Prophylaxis For Long-term Visitors and Frequent Visitorsmentioning
confidence: 99%
“…57 In contrast, mefloquine use among US service members from 2002-2004 was not associated with severe health effects. 58 Mefloquine was well tolerated when used for more than 3 months in Italian soldiers in Somalia and Mozambique 59 as well as in Peace Corps Volunteers, where it was used for up to 2.5 years. 48 Only 0.3% of Dutch marines who used mefloquine for 6 months reported adverse effects requiring medical attention.…”
Section: Safety Of Malaria Chemoprophylaxis For Long-term Travelmentioning
confidence: 99%